Fungi as biocontrol agents in nature: Interaction of fungi on phylloplane of Datura metel L. and Vigna catjang L. - Shamsi, Shamim; Naher, Najmun; Haq, Rokeya (Bangladesh Journal of Agricultural Research, 2012)
Bangladesh J. Agril. Res. 37(3): 537-541, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12130